Herschel Observations of the HR 8799 Disk. Issue Volume 8:Issue S299(2013) (6th January 2014) - Matthews, Brenda C.; Kennedy, Grant; Sibthorpe, Bruce; Booth, Mark; Broekhoven-Fiene, Hannah; Wyatt, Mark; Macintosh, Bruce; Marois, Christian
Abstract: The HR 8799 four-planet host is known to host a multi-component disk from Spitzer observations. We have obtained Herschel † observations of the disk which provide increased sensitivity and resolution of its outer components: the planetesimal belt and halo. We find that the two components cannot be discerned from the spectral energy distribution alone, but require resolved images to independently identify them. In the resolved images, the halo stands out for its steep radial profile and large radial extent to 2000 AU, a factor of two larger than was estimated from Spitzer data.